Antisites disorder mediated magnetization relaxation and polydispersity in La2NiMnO6 crystallites - Hissariya R.; Sharma R.; Mishra S.K. (My University, 2025)
Antisite disorders play a critical role in determining the magnetic ground state of the La2NiMnO6 double perovskite compounds that show multifunctional behaviours and spin-glass phases at lower temperatures. The spin-glass (SG) state and magnetization relaxation in these compounds have been studied extensively; however, the polydispersity of the SG state remains elusive. Employing ac-magnetic susceptibility χ(ω,T) and temperature-dependent electron spin resonance (ESR) spectroscopy, herein, we probe the polydispersity of the SG phase in La2NiMnO6 crystallites. We employed X-ray photoelectron spectroscopy (XPS) to -investigate the crystallite size-dependent variable fractions of Mn3+/Mn4+ (Ni2+/Ni3+) cations and their influence on completing exchange interactions. Mn-2p core-level XPS spectra suggest a dominant Mn4+ + Ni2+→Mn3+ + Ni3+ charge transfer peak that appeared as a satellite peak at lower binding energy than the Mn core-level. The observed differences in saturation magnetization (MS) as a function of crystallite size indicate the variation in the degree of antisites disorder. Competing magnetic interactions driven by mixed valence and disorder facilitate a spin-glass (SG) phase at lower temperatures. Utilizing ESR measurement across paramagnetic → competing ferro/antiferromagnetic phase, a modified g-factor that ranges from 2.050-2.037 is observed in the paramagnetic region. The line width of the ESR signals is found to be increased across the transition suggesting spin-freezing characteristics. Cole-Cole plots obtained from χ(ω,T) data indicate collective spin relaxation dynamics in the proximity of the freezing temperature. Our findings suggest the importance of the size effect and its relation with the degree of antisites disorders in these crystallites. These experimental results enable the La2NiMnO6 compound to find its possible applications in new areas of material research. © 2023 Elsevier Ltd